Adaptive Doppler compensation method for coherent LIDAR based on optical phase-locked loop. (January 2022) - Ren, Ning; Zhao, Bin; Liu, Bo; Hua, Kangjian
Graphical abstract: Highlights: An optical phase-locked loop is used at the coherent LIDAR receiver for phase synchronization. The variable and large Doppler frequency shift can be adaptively compensated by an optical phase-locked loop. The coherent LIDAR can detect the high-speed target and the variable speed target. Abstract: Coherent LIDAR is a potential and effective technology to detect and identify space debris. However, for the high-speed space debris, the large Doppler frequency shift (DFS) generated by high-speed relative motion challenges the bandwidth of the photoelectric detection system and increases the difficulty of data sampling and processing. In this paper, we propose an effective method to compensate this large DFS adaptively by using an optical phase-locked loop (OPLL), and thus the relative velocity between the target and LIDAR platform can be obtained. A laboratory experiment for moving targets with our OPLL method has been conducted, and it revealed that our method worked well to compensate for 64 MHz frequency difference, thus the relative velocity is about 26 m/s based on the compensated DFS. And the beat frequency is always locked to the reference frequency, while the DFS generated by variable speed motion is compensated adaptively. The proposed compensation method could improve the performance of coherent LIDAR significantly, especially when detecting high-speed target.